2020
DOI: 10.1007/978-3-030-64834-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Unbounded HIBE with Tight Security

Abstract: We propose the first tightly secure and unbounded hierarchical identity-based encryption (HIBE) scheme based on standard assumptions. Our main technical contribution is a novel proof strategy that allows us to tightly randomize user secret keys for identities with arbitrary hierarchy depths using low entropy hidden in a small and hierarchy-independent master public key.The notion of unbounded HIBE is proposed by Lewko and Waters (Eurocrypt 2011). In contrast to most HIBE schemes, an unbounded scheme does not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Game H 2,c,1 : In H 2,c,1 , instead of generating a random t in O Mac , we choose t from Span(B B 0 ) (if hm j+1 = 0) or Span(B B 1 ) (if hm j+1 = 1). This is the same step as Lemma 17 of [29]. By basis for Z 3k q basis for Span(B ⊥ )…”
Section: A Proof Of Theoremmentioning
confidence: 83%
See 1 more Smart Citation
“…Game H 2,c,1 : In H 2,c,1 , instead of generating a random t in O Mac , we choose t from Span(B B 0 ) (if hm j+1 = 0) or Span(B B 1 ) (if hm j+1 = 1). This is the same step as Lemma 17 of [29]. By basis for Z 3k q basis for Span(B ⊥ )…”
Section: A Proof Of Theoremmentioning
confidence: 83%
“…To overcome this issue, we borrow recent techniques from tightly-secure hierarchical identitybased encryption schemes [28,29] to construct a new MAC scheme that can be proven tightly secure under adaptive corruptions. Our construction is based on pairings and general random self-reducible matrix Diffie-Hellman (MDDH) assumptions [18].…”
Section: Introductionmentioning
confidence: 99%
“…By its random self-reducibility [EHK + 13, Lemma 1], the 2-fold U 3,1 -Matrix-DDH (MDDH) assumption (namely, the uDDH3 assumption) is tightly equivalent to the U 3,1 -MDDH assumption. By Lemma 1 in [LP20], U 3,1 -MDDH is tightly equivalent to U 1 -MDDH that is the DDH assumption. Hence, the DDH and uDDH3 assumptions are tightly equivalent.…”
Section: Definition 7 (Ddh Assumption) Letmentioning
confidence: 96%
“…On the other hand, in [15], [27], [28], the authors showed a CPA-to-CCA2 transformation for (not leakageresilient) IBE schemes by using a simulation-sound (tagbased) QA-NIZK argument for linear subspaces. At first glance, thanks to the public verifiability of the QA-NIZK argument, their approach seems to provide LR-CCA2-secure schemes by only replacing the CPA-secure schemes with LR-CPA-secure ones.…”
Section: Technical Overviewmentioning
confidence: 99%